Rights and Citizenship in the European Union - Dennis C. Mueller (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper employs the methodology of constitutional political economy to examine the definition of citizenship, and the delineation of the rights that accompany citizenship. The concepts developed are then applied to the question of how rights and citizenship should be defined in the European Union. The answer to this question is shown to depend on whether the Union is organized as a federation or a confederation. The concepts developed are then used to critique the Charter of Fundamental Rights of the European Union, and to question whether this Charter should be made a part of a new European Union constitution.
Keywords: 330